Traditional Revolt against the Modern Science (Philosophy in the Inter-war Period) - Marek Jedliński (Ksiegarnia Akademicka Publishing, 2021)
The article presents the views of traditionalists of the interwar period on science and education. Traditionalist philosophy is characterized by a turn to the past and a desire to return to the old world; the modern era is severely criticized. From this perspective, traditionalists contest the science of the modern world. According to them, it is characterized by a one-sided development, which has also affected the Western education system. Traditionalist philosophy denounces the rationalism and pragmatism inherent in modern science, proposing an alternative vision of traditional science based on wisdom rather than expert knowledge. According to traditionalists, science based on the affirmation of novelty and the unknown can threaten tradition – the transmission of the highest values, ideas and goals, without which no culture can survive.